Return to roots. Vladimir Sorokin’s zaum - Mięsowska, Lidia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article is an attempt to show connections of Vladimir Sorokin with OBERIU’s tradition as well as Russian futurism. The dramatist experiments with language creating his own version of postmodern zaum, thanks to that he can be called a real “word manipulator” (D. Tokariev). In this way Sorokin is always situated on the border of two orders: the past and the future one. At the same time he is an inheritor and continuator of Daniil Kharm’s theatre of the Absurd, on the other hand he is also an innovator who introduces dramatic genre into the stage of surprising, aesthetic experiments.